Substrate‐Adatom Interface Engineering of Transition Metal Decorated Boron‐Doped Graphene Sheet for Enhanced Adsorption of Xe and Kr – A Systematic Ab initio Study. Issue 9 (8th August 2021) - Pazhedath, Anees
Abstract: Efficient adsorption and segregation of Xe and Kr gases are of high importance in commercial and nuclear industries. Systematic ab initio calculations reveal that transition‐metal (TM) decorated boron‐doped graphene (BDG‐TM) sheet can act as an efficient substrate for adsorptive capture of Xe and Kr (adatoms). Substantial enhancement in the adsorption energy ( E ads ) is obtained on BDG‐TM substrates, and it varies as BDG‐Cu > BDG‐Ni > BDG‐Fe > BDG‐Zn. The improvement is approximately four times that of the pristine BDG and twice that of the conventional metallic substrates. TM‐decoration alters the charge distribution at the substrate‐adatom interface, which brings a considerable change in the polarization and induced dipole moment of adatom, leading to significant improvement in the E ads . Partial density of states analysis shows a splitting and significant interaction of Xe‐p with TM‐d orbitals near the Fermi level of Fe, Ni, and Cu decorated systems, unveiling strong adsorption. Further, the effect of clustering and dispersion of Cu atoms on E ads are analyzed using a first‐principle‐based genetic algorithm, which reveals that clustering of Cu atoms deteriorates the E ads of Xe and Kr. Thus, for experimental realization, a BDG sheet with uniformly dispersed fine Cu particles is proposed as a substrate. Abstract : Ab initio calculations reveal a substantial enhancement in the adsorption energy ( E ads ) of Xe and Kr on transition metal decorated boron‐doped graphene (BDG‐Fe/Ni/Cu) substrates, which is approximately twice that of the upper bounds of E ads obtained on conventional metallic, metal organic frameworks, and 2D material substrates.